SISTEM INFORMASI PERKULIAHAN MENGGUNAKAN FASILITAS SMS PADA JARINGAN GSM - Hermawi, Adrianto; Budi. M, Pono; Sasmitha, Dharma (Universitas Tarumanagara, 2008)
At present of time, development of information and technology has become more modern. This growth affect of human life style. One of the causalities has effect in the environment university college. These life style changes are to be motivated at this final project. These system objectives are student of University College. This system supports an SMS message. This message will appear in the monitor computer. These systems also have a database, in which the message send from the lecturer will be store in the computer. A GSM mobile telephone used in this system design (only the GSM network will work at this system), although this system work only with GSM but this system also receive a SMS message from CDMA network (only receive).